An ultraviolet dyegraph for measuring the chemical disturbances of sinking particles and swimming plankton. (19th October 2020) - Inman, Bryce G.; Franks, Peter J. S.; Roberts, Paul L. D.
Abstract: Sinking particles and swimming plankton may deform ambient chemical gradients, leaving long trails of chemical disturbance that dissipate on a diffusive timescale. Imaging this phenomenon in a laboratory setting requires a large field of view, a broad depth of field, and a passive chemical substance that does not influence the hydrodynamics. These requirements obviate the use of traditional schlieren optical systems, which rely on density stratification and their consequent buoyancy forces, and modern planar laser‐induced fluorescence, which has a narrow depth of field. Further, the light used to induce plankton movement must be kept separate from the recorded signal. Here, we describe a new ultraviolet "dyegraph" technique that quantifies dye disturbance caused by sinking spheres and swimming zooplankton. An experimental tank is filled with seawater and a gradient of an ultraviolet‐absorbing pigment. Using modified shadowgraph optics, ultraviolet light spreads from a pinhole to a collimating lens, passes through the tank to a telecentric lens, and is recorded by a camera fitted with an ultraviolet bandpass filter. The dye is transparent in visible light but appears dark in the imaging system. The 3D chemical disturbance is reconstructed from images using tomographic inversion. After outlining the method, we present examples of chemical deformation trails generated by sinking spheres and live, swimming copepods.